ChemInform Abstract: The Neat Ternary Solid K5‐xCo1‐xSn9 with Endohedral [Co@Sn9]5‐ Cluster Units: A Precursor for Soluble Intermetalloid [Co2@Sn17]5‐ Clusters. Issue 1 (3rd January 2013) - Hlukhyy, Viktor; He, Haiyan; Jantke, Laura‐Alice; Faessler, Thomas F.
Abstract Crystal structures of compounds (IV) and (V) are determined by single crystal XRD.